Footprints of the COVID-19 Pandemic on Higher Education - AYYILDIZ, Pınar; YILMAZ, Adem (Uludag Universitesi Egitim Fakultesi Dergisi, 2022)
This research examined the effects and reflections of the COVID-19 Pandemic in Higher Education were examined. Participants were 1166 university students studying in different departments were determined using convenient sampling method. The survey method, which is one of the quantitative research approaches, was used in the research process. As the data collection tool, a Likert-type scale with 5 factors and 45 questions was employed by the researchers. Research data were analyzed using IBM SPSS 24.0 and IBM AMOS 24.0. Descriptive and inferential statistical techniques were used in the analysis of the research data. Independent samples t-test, one-way ANOVA test, and correlation test were performed in inferential statistical analysis. Confirmatory factor analysis was carried out for the construct validity of the scale. The mediation effect for scale dimensions was tested with serial multiple mediation effect analysis using HAYES's model number 6. As a result of the research, the opinions of university students showed a significant difference apropos of gender, grade level, and department variables. The highest attitude tendency was in the CVEP (COVID-19 Vaccine and Education Process) dimension and the lowest in the ATDE (Attitude towards Distance Education) dimension. The attitudes of university students toward distance education indirectly affect the mediating impact of the variables viz. faculty members' activities, technical infrastructure as well as the variables of the measurement and evaluation system, the Covid-19 vaccine and the process.
Keywords: 4. Education; 10. No inequality; 16. Peace & justice; 3. Good health